Pengaruh Perbandingan Eceng Gondok Dan Air Terhadap Kestabilan Sistem Pada Produksi Biogas Secara Fermentasi Anaerob Tahap Metanogenesis - Resti Ossi P; Adrianto Ahmad; Sri Rezeki Muria (Jurnal Online Mahasiswa (JOM) Bidang Teknik dan Sains, 2015)
Hyacinth (Eichhorhia crassipes) is a weed on waters which is a big problem for damage the environment but it contains materials that can be fermented and produce biogas, there are hemicellulose and cellulose. This research head for produce biogas from hyacinth by anaerob fermentation process with microorganizm on batch system and determine optimum ratio of hyacinth and water along with the effect to the stability of system. There were stages on this research, including seeding, acclimatization, and anaerob batch fermentation. Seeding was doing in ten days with ratio hyacinth and water was 75%:25%, then continued to acclimatization in 48 days. The anaerob batch fermentation was doing with variation of ratio hyacinth and water 1:2, 1:3, 1:4, and 1:5 in anaerob batch bioreactor during 32 days. Analysis of pH, biogas volume, volatile acid, and alkalinity was analized every two days during anaerob batch fermentation. The result of this research showed that in 48 days acclimatization process was produced biogas about 75.840 mL. In the fermentation process was resulted biogas about 23.300 mL with methane contents was 11.924,56 ppm or 1,19%; pH optimum 6,8-7,2; volatile acid concentration 145,8 mg/L; alkalinity concentration 1684,13 mg/L, and ratio of AV/alkalinity 0,087 on the rasio of hyacinth and water at 1:2. In conclusion, the stability of system will decrease along with increasing amount of water in the substrat of anaerob batch fermentation.Keywords: Anaerob Batch Fermentation, Biogas, Hyacinth, Methane